Etika Profesi TI di Era AI: Tantangan Perlindungan Data dan Privasi Pengguna - Syarifuddin, Syarifuddin; Arpan Mualief Saprizal; Risky Pebriana; Tira Margaret; Liliana Swastina (Majalah Ilmiah METHODA, 2025)
The era of artificial intelligence (AI) has brought fundamental transformations in various aspects of life, including the Information Technology (IT) profession. Along with rapid innovation, complex ethical challenges have emerged, particularly regarding data protection and user privacy. This paper examines the ethical implications of the application of AI in the IT context, with a focus on how IT professionals can navigate the moral dilemmas that arise from the collection, processing, and use of data at scale. We analyze existing ethical frameworks and identify the need for new guidelines to ensure the responsible and ethical development and implementation of AI. The ultimate goal is to provide practical recommendations for IT professionals, organizations, and policymakers in addressing ethical challenges in the AI ​​era, in order to maintain public trust and ensure individual rights.